Multiple parafoveal retinal detachment in myopic tractional maculopathy - Tsai-Chu Yeh; Shih-Jen Chen (Taiwan Journal of Ophthalmology)
This study investigates the occurrence of multiple parafoveal retinal detachments (RDs) in myopic traction maculopathy (MTM), emphasizing the atypical extrafoveal involvement compared to central foveal detachment commonly observed. Patient 1, a 46-year-old male, exhibited MTM with retinoschisis and four small subretinal fluid (SRF) pockets inferior to the fovea, accompanied by a hyperautofluorescent vitelliform deposit. Patient 2, a 43-year-old male, reported ring-shaped dim vision in the left eye, displaying MTM with six stable SRF pockets surrounding the fovea. These SRF pockets maintained a stable size ranging from 173 to 1140 um in diameter over the course of a 5-year follow-up period. Interestingly, fluorescein and indocyanine angiography showed no leakage or hyperpermeability in both cases. The study highlights the necessity for a comprehensive exploration of extrafoveal RDs in MTM, challenging conventional expectations. The mechanism of these persistent extrafoveal detachments associated with myopic schisis was unknown. The findings prompt further research to unravel the intricate mechanisms of this rarely reported phenomenon, emphasizing the importance of expanding our understanding of extrafoveal manifestations in eyes with MTM.